Efficient three variables reversible logic synthesis using mixed-polarity Toffoli gate - Cheng, C.; Singh, A.; Gopal, Lenin (ELSEVIER SCIENCE BV, 2015)
In this paper, we present an efficient reversible logic synthesis algorithm that uses Toffoli and mixed-polarity based Toffoli gate. In this paper, we propose an algorithm to synthesizereversible function in their positive-polarity Reed Muller (PPRM) expansion and usethe Hamming Distance (HD) approach to select suitable transformation path. Once a transformation path is defined, suitable gates for substitution are selected through the gate matching factor and reduction is performed. The algorithm does not generate any extra lines and thus keeping the synthesized function in its simplest form. The algorithm target on efficient way to synthesize three variables based reversible function into a cascade of Toffoli and mixed-polarity based Toffoli gate in term of quantum cost and gate count. Experimental results showthat the proposed algorithm is efficient in terms of the realization of all three variable based reversible functions